Rubella virus infection in endothelial cells reduces angiogenesis via interferon beta-induced CXCL10 - Henschke, Vivien; Hild, Konstanze; Schilling, Erik; Haas, Jan; Filipova, Vanina; Erbe, Stephan; König, Roman; Hübschen, Judith M.; Laufs, Ulrich; Claus, Claudia; Boeckel, Jes-Niels (iScience, 2023)
Rubella virus (RuV) infection during pregnancy can lead to abortion, stillbirth, and embryonic defects, resulting in congenital rubella syndrome (CRS). It is estimated that there are still 100,000 cases of CRS per year in developing regions with a mortality rate of over 30%. The molecular pathomechanisms remain largely unexplored. Placental endothelial cells (EC) are frequently infected with RuV. RuV reduced the angiogenic and migratory capacity of primary human EC, as confirmed by treatment of EC with serum from RuV IgM-positive patients. Next generation sequencing analysis revealed the induction of antiviral interferon (IFN) type I and III and CXCL10. The RuV-induced transcriptional profile resembled the effects of IFN-β treatment. The RuV-mediated inhibition of angiogenesis was reversed by treatment with blocking and neutralizing antibodies targeting CXCL10 and the IFN-β receptor. The data identify an important role for antiviral IFN-mediated induction of CXCL10 in the control of EC function during RuV infection.